2011
DOI: 10.1021/jm2002958
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Hydrophilic Linkers for Antibody–Maytansinoid Conjugates

Abstract: The synthesis and biological evaluation of hydrophilic heterobifunctional cross-linkers for conjugation of antibodies with highly cytotoxic agents are described. These linkers contain either a negatively charged sulfonate group or a hydrophilic, noncharged PEG group in addition to an amine-reactive N-hydroxysuccinimide (NHS) ester and sulfhydryl reactive termini. These hydrophilic linkers enable conjugation of hydrophobic organic molecule drugs, such as a maytansinoid, at a higher drug/antibody ratio (DAR) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 41 publications
11
153
0
Order By: Relevance
“…1A and Scheme S1). The linker contains two ethylene glycol moieties modified with a terminal alkoxy-amine group to improve solubility and minimize export of the more hydrophilic derivatized analogs by drug pumps (32).…”
Section: Resultsmentioning
confidence: 99%
“…1A and Scheme S1). The linker contains two ethylene glycol moieties modified with a terminal alkoxy-amine group to improve solubility and minimize export of the more hydrophilic derivatized analogs by drug pumps (32).…”
Section: Resultsmentioning
confidence: 99%
“…-(4-mercapto-4-methyl-1-oxopentyl)-maytansine (DM4) via the succinimidyl-4-(N-maleimidomethyl)cyclohexane-1-carboxylate (SMCC), the N-succinimidyl 4-(2-pyridyldithio)pentanoate (SPP), the N-succinimidyl 4-(2-pyridyldithio)butanoate (SPDB), or the N-succinimidyl 4-(2-pyridyldithio)-2-sulfobutanoate (sulfo-SPDB) linkers according to the protocols developed at ImmunoGen, Inc. and described previously (31)(32)(33). The maytansinoid per antibody ratio varied from 3.3 to 5.0.…”
Section: Cell Linesmentioning
confidence: 99%
“…Humanized anti-folate receptor-a (FRa), anti-EGFR, and anti-CD33 antibodies, chimeric mouse-human anti-EpCAM antibody, and chimeric non-binding control antibody to the Kunitz soybean protease inhibitor (KTI) were all constructed with the human IgG 1 isotype and generated at ImmunoGen, Inc. None of the antibodies used in the studies cross-react with antigen on mouse tissues. The antibody modifying agents SPDB [N-succinimidyl 4-(2-pyridyldithio)butanoate] and sulfo-SPDB [N-succinimidyl 2-sulfo-4-(2-pyridyldithio) butanoate] were prepared as previously described (20,21). Additional chemical reagents were purchased from Sigma-Aldrich.…”
Section: Cell Lines Antibodies and Reagentsmentioning
confidence: 99%
“…We have previously shown that incorporation of a sulfonate group in the disulfide linker confers improved water solubility to maytansinoid ADCs and also enhances antitumor efficacy in vivo (21,29). By analogy, we incorporated the charged sulfonate group in the IGN ADCs as part of the linker optimization effort.…”
Section: Linker Optimization and In Vivo Antitumor Activitymentioning
confidence: 99%